Ethno-ornithology and conservation: traditional ecological knowledge (TEK) of birds among the Mushere and the conservation of the Dulu forest in Mushere, Plateau state, Nigeria - Pam, G (2017)
This research was aimed at determining the ethno-ornithological knowledge of three Mushere villages close to the Dulu Forest, Nigeria to determine whether this might hold potential for developing a local conservation programme to protect the forest. The conservation objective of the research was aimed at determining the drivers of forest degradation, and possible means of mitigation. Using a mixed method approach, quantitative/qualitative data were collected in two years from different demographics (men, women, children, age differentials, occupation, urbanization). Oral interviews, semi-structured interviews, picture elicitation tasks, free-listing exercises and focus group discussions were employed in the data collection process. The findings revealed a relatively low ethno-ornithological knowledge, and a general indifference (ornitho-apatheia) towards birds. Knowledge transmission was predominantly through oral means while TEK acquisition was mainly through vertical and horizontal methods. While adults perceived birds as not valuable, children generally perceived birds as valuable. Cultural utilization and ecological salience were the main drivers of bird naming and knowledge. However, there was a high valuing of the Dulu forest, with the main drivers of the forest degradation being timber extraction. Overall, I concluded that the indifference of the Mushere towards birds revealed a lack of cultural appreciation of birds, leading to little TEK of birds, insufficient to encourage the use of TEK of birds in the conservation of the Dulu forest, and the use of birds as flagship domain for promoting conservation. However, a sustained approach towards encouraging birding activities could improve the perception of birds. I therefore suggest using an ecosystem approach in the conservation of the Dulu forest. Engaging the locals in dialogue, establishing a leadership structure for the management of the Dulu forest, providing alternative means of livelihoods are suggested as ways of mitigating the degradation of the Dulu forest.